The Experience of Reading the Church Fathers in the Post$modern Context - Zaprometova, Olga (Bogoslovskie razmyšlenija, 2009)
The paper represents the attempt of comparative analysis of the spiritual experiences of the Church Fathers, expressed by them in the development of their doctrine on the divine light and theosis, and Pentecostalism, insisting on the importnace of the Holy Spirit's experience for every new born Christian. The examples from Gregory the Theologian (IV century) and Simeon the New Theologian (X-XI centuries) prove us the importance of the personal experience of the common faith, pointing to the continuity and the development of the mystical theology of the Eastern Church. The author raises the question of acquisition of the patristic heritage by the contemporary Russian Pentecostalism and of the possible ways of its further development.